2019
DOI: 10.1530/edm-19-0028
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of thyroid gland invasion by upper mediastinal carcinoma

Abstract: Summary The objective this study is to report two cases of thyroid gland invasion by upper mediastinal carcinoma. Mediastinal tumors are uncommon and represent 3% of the tumors seen within the chest. In reports on mediastinal masses, the incidence of malignant lesions ranged from 25 to 49%. The thyroid gland can be directly invaded by surrounding organ cancers. We report these cases contrasting them to the case of a thyroid cancer with mediastinal lesions. Case 1 was a 73-year-old woman who was diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Using laryngoscopy, gastroscopy, CT scan, or systemic PET-CT, the possibility of secondary thyroidal squamous cell carcinoma can be ruled out (18)(19)(20). Cellular markers such as p63, PAX8, CK7, CK19, CK20, TG, and TTF-1, can also be used to help diagnose PSCCT (5,8). In our study, all patients were diagnosed with PSCCT using histopathology which showed a palisade arrangement, intercellular bridges, and keratinization with a cancer pearl.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using laryngoscopy, gastroscopy, CT scan, or systemic PET-CT, the possibility of secondary thyroidal squamous cell carcinoma can be ruled out (18)(19)(20). Cellular markers such as p63, PAX8, CK7, CK19, CK20, TG, and TTF-1, can also be used to help diagnose PSCCT (5,8). In our study, all patients were diagnosed with PSCCT using histopathology which showed a palisade arrangement, intercellular bridges, and keratinization with a cancer pearl.…”
Section: Discussionmentioning
confidence: 99%
“…These PSCCT characteristics also make it difficult to achieve negative margins during radical resection of the tumor. Because of the difficulties of removing PSCCT surgically and its lack of sensitivity to radiotherapy or chemotherapy, patients with PSCCT have an extremely poor prognosis, with median survival times after diagnosis of only 5-8 months (5,6). The clinical behavior of PSCCT resembles anaplastic thyroid carcinoma, another difficult to treat tumor of the thyroid with a poor prognosis (3,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these diagnostic procedures are difficult in ectopic thyroid glands in the mediastinum because of anatomical complexity (presence of bones and lungs). We have encountered and reported two cases of patients with mediastinal tumors that were not thyroid cancers and were diagnosed after biopsy by bronchoscopy, immunohistological examination for PAX-8, thyroglobulin, and TTF-1 [5].…”
Section: Case Reports In Endocrinologymentioning
confidence: 99%